ANALISIS TEOLOGIS MISI BIROKRAT KRISTEN DALAM PEMERINTAHAN - Harun, Harun; Manguling, Sulaiman; Kadang, Yan Kristianus; Suardana, I Made; Tari, Ezra (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
The purpose of this study is to theologically analyze the mission of Christian bureaucrats in the Office of the Ministry of Religious Affairs of North Toraja Regency. Through qualitative research methods with observation and interview techniques, it was found that the mission of the church in the government bureaucracy has not been visible, not because of the tendency of Christian bureaucrats to see the relationship between church and government in the framework of the third relationship (total separation), but there are still Christian bureaucrats who see it in the framework of the first relationship (state supremacy over the church). In addition, another influencing factor is that their understanding of mission is still traditional and inherits colonial understanding. However, in general, Christian bureaucrats understand that the relationship between church and government should be seen in terms of partnership, but it is not enough to reach the stage of understanding. Therefore, building a critical-prophetic, positive, creative, and realistic partnership between the church and the government through the mission of Christian bureaucrats is one of the church's mission strategies that needs serious attention and focus. It is important that every Christian who is hypostatized into Christ through the church wherever they are, should act in an eucharistic and sacramental way. Thus, the public sphere and the ecclesiastical sphere are intertwined.